Urban Politics of Human Rights - Nijman, Janne; Oomen, Barbara; Durmuş, Elif; Miellet, Sara; Roodenburg, Lisa (Cities and Global Governance, 2023)
Increasingly, urban actors invoke human rights to address inequalities, combat privatisation, and underline common aspirations, or to protect vested (private) interests. The potential and the pitfalls of these processes are conditioned by the urban, and deeply political. These urban politics of human rights are at the heart of this book. An international line-up of contributors with long-term engagement in this field shed light on these politics in cities on four continents and eight cities, presenting a wealth of empirical detail and disciplinary theoreticalisation perspectives. They analyse the 'city society', the urban actors involved, and the mechanisms of human rights mobilisation. In doing so, they show the commonalities in rights engagement in today's globalised and often deeply unequal cities characterised by urban law, private capital but also communities that rally around concepts as the 'right to the city'. Most importantly, the chapters highlight the conditions under which this mobilisation truly contributes to social justice, be it concerning the simple right to presence, cultural rights, accessible housing or - in times of COVID - health care. Urban Politics of Human Rights provides indispensable reading for anyone with a practical or theoretical interest in the complex, deeply political, and at times also truly promising interrelationship between human rights and the urban.